Locality vs Globality: Wayang Sasak's Practice and Teaching in the World Literature - Habiburrahman, Lalu (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This research aims to examine the issue of the relationship between locality and globality which is the practice of Sasak puppets in teaching global literary values. The research was conducted on the work on the play Brambang Ulung, one of Amir Hamzah's series of stories in the Sasak puppet. The method combines ethnographic studies, video recordings, literature reviews and interviews. Processing the data using the movie avi 15 plus and excel. This research applies discourse analysis and representation of the Bourdieusian model. Data analysis showed that the field practice lasted all night around 6:56:21 (six hours and fifty-six minutes and twenty-one seconds, divided into preparation, 0.27:20 or 6.75%; modal gending with a duration of 1:30:47 or 21.80%; and the play modal with a duration 4:58:18 or 71.63%. The analysis of the play modal with a duration of 4:58:18, found the main play modal is in Middle Javanese language, 2:35:51 or 52.26%; the intermediate play modal is in Middle Javanese and Sasak language, with time duration 0:52:40 or 17.66%; and Sasak language play modal with a duration of 1:29:43 or 30.08%. This study reveals the global (Arabic) literary value of Amir Hamzah's story, including da'wah. This practice is a legacy of local teaching networks and pre-modern global. Ricci termed this network with Arab Kosmopolis, a literary network that forms a network of ummah. Pre-modern models of local and global relations, such as in the field practice of Sasak puppets, appear grounded. This is different from the model in local textbooks, wayang Sasak and other local contexts are taught as complementary.